APICA: 18 years of robust service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The Association for the Promotion of African Community Initiatives (APICA) is an international association recognised under Swiss law. It was established in 1980 with the objective of supporting development initiatives in rural and urban areas in...